Estudio de pre-factibilidad para la implementación de una empresa productora y comercializadora de dulce de leche de cabra en la ciudad de Loja, año 2022 - Córdova Córdova, Jéssica Stefanía (2023)
The pre-feasibility study for the implementation of a company that produces and markets of goat milk sweet in Loja City, raised the following objectives: carry out a market study to determine supply, demand and define marketing strategies; determine the technical, administrative and legal requirements; calculate the investment, find the best source of financing, prepare the income and expense budgets and the financial statements and; determine financial feasibility according to financial indicators, VAN, IRR, recovery period, benefit-cost ratio, sensitivity analysis. The type of research is descriptive, methods that helped to collect information were used. The segment of the population chosen were the families of the city of Loja, the total population of the same is 58,266 families, the population growth rate is 2.65%, while the size of the sample was 382 families, which were surveyed. It has been determined that the project is profitable based on the following results: the Net Present Value (VAN) is $41,576.02; the Internal Rate of Return (IRR) is 43.96%; while the Capital Recovery Period is 3.14, which means that the company will recover its investment in 3 years, 1 month and 19 days; the Cost Benefit Ratio (RBC) is 1.16, which means that for each dollar invested the company will have a profit of 0.16 cents, the Sensitivity Analysis with increased costs is 0.9960, also emphasizing that only it can increase costs by 4.85%, while due to a decrease in income it is 0.9989, saying in turn that the company can support a decrease of up to 4.87% in its income. Thus, it is considered that the project is profitable and viable.